Powerful association test combining rare variant and gene expression using family data from Genetic Analysis Workshop 19. Issue 7 (October 2016) - Ho, Yen-Yi; Guan, Weihua; O'Connell, Michael; Basu, Saonli
Abstract Background Genetic association studies aim to test for disease or trait association with genetic variants, either throughout the human genome or in regions of interest. However, for most diseases and traits, the combined effects of associated genetic variants explain only a small proportion of the genetic variation. This "missing heritability" may be a result of the small effects of common variants considered in the genetic association studies. Rare variants may also play an important role in understanding the missing heritability of complex traits. Method We propose a novel weight-adjustment approach to combine gene expression into rare variant analysis. Results from previous simulation studies suggested that incorporating gene expression information can lead to substantial gain in statistical power. Results Using the family data set provided through the Genetic Analysis Workshop 19, we identified susceptible genes associated with blood pressure regulation. Conclusions These findings provide valuable information for further functional studies for blood pressure control and mechanism.